Cover Image. Issue 3 (16th June 2020) - De La Rosa, Vanessa Y.; Hoover, Joseph; Du, Ruofei; Jimenez, Elizabeth Yakes; MacKenzie, Debra; ,; Lewis, Johnnye
Abstract : The cover image is based on the Original Article Diet quality among pregnant women in the Navajo Birth Cohort Study by Vanessa Y. De La Rosa et al., https://doi.org/10.1111/mcn.12961 .